Using click-evoked auditory brainstem response thresholds in infants to estimate the corresponding pure-tone audiometry thresholds in children referred from UNHS. (April 2017) - Lu, Tsun-Min; Wu, Fang-Wei; Chang, Hsiuwen; Lin, Hung-Ching
Abstract: Objective: To examine whether behavioral pure-tone audiometry (PTA) thresholds in children can be accurately estimated from the corresponding infants' click-evoked auditory brainstem response (ABR) thresholds through a retrospective review of data from a universal newborn hearing screening (UNHS) program in Taiwan. Method: According to medical records from Mackay Memorial Hospital, Taipei Hospital District, 45, 450 newborns received hearing screening during January 1999–December 2011. Among these newborns, 104 (82, both ears; 22, one ear; total, 186 ears) received regular follow-up and were recruited as subjects. The relationship between infant click-evoked ABR thresholds and the corresponding child PTA thresholds was determined through Pearson correlation coefficient and linear regression analyses. Results: The correlation coefficient between click-evoked ABR thresholds and behavioral PTA thresholds at the average of frequencies of 1–4 and 2–4 kHz was 0.76 and 0.76, respectively. Linear regression analysis showed that behavioral audiometry thresholds at the average of frequencies of 1–4 and 2–4 kHz were accurately estimated from click-evoked ABR thresholds in 57% and 58% children, respectively. Conclusion: Click-evoked ABR testing is a reliable tool to cautiously estimate behavioral PTA thresholds at the average of frequencies of 1–4 and 2–4 kHz. For accurately performing hearing aid fitting and auditory rehabilitation in congenitally deaf infants, a combination of frequency-specific tone-burst ABR and click-evoked ABR should be used.